2021
DOI: 10.1002/anie.202102074
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Evolution of Antivirals Against Enterovirus D68 through Protein‐Templated Knoevenagel Reactions

Abstract: The generation of bioactive molecules from inactive precursors is ac rucial step in the chemical evolution of life, however,mechanistic insights into this aspect of abiogenesis are scarce.Here,weinvestigate the protein-catalyzed formation of antivirals by the 3C-protease of enterovirusD 68. The enzyme induces aldol condensations yielding inhibitors with antiviral activity in cells.K inetic and thermodynamic analyses reveal that the bioactivity emerges from ad ynamic reaction system including inhibitor formatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Considering the high variability of virus and the complexity of pathogenic mechanisms, DNA-encoded chemistry technology [ 39 ], genome editing technology [ 40 ], nucleic acid aptamer technology [ 41 ] and ligand discovery based on protein self-assembly [ 42 ] are expected to provide references for the development of potent antiviral drugs. Moreover, natural products have complex structures and diverse physiological activities, providing unlimited resources to discover novel antiviral drugs [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the high variability of virus and the complexity of pathogenic mechanisms, DNA-encoded chemistry technology [ 39 ], genome editing technology [ 40 ], nucleic acid aptamer technology [ 41 ] and ligand discovery based on protein self-assembly [ 42 ] are expected to provide references for the development of potent antiviral drugs. Moreover, natural products have complex structures and diverse physiological activities, providing unlimited resources to discover novel antiviral drugs [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous works, we and others have demonstrated that peptidomimetics containing glutamine residues or their lactam derivatives can be replaced successfully by druglike inhibitory fragments. Typically, these fragment inhibitors contained an aromatic amide such as benzamide or an amino‐pyrazoline fragment for targeting the S1 pocket and a reactive electrophile such as a Michael acceptor, epoxide, vinyl sulfonamide, or an aromatic ketone for targeting the nucleophilic cysteine residue [6b,12] . Several of these fragments displayed broad‐band inhibition of 3C and 3CL proteases [12a] and some were active in cellular virus proliferation assays, depending critically on the binding kinetics and chemical stability of the inhibitors [6b] .…”
Section: Introductionmentioning
confidence: 99%
“…Typically, these fragment inhibitors contained an aromatic amide such as benzamide or an amino‐pyrazoline fragment for targeting the S1 pocket and a reactive electrophile such as a Michael acceptor, epoxide, vinyl sulfonamide, or an aromatic ketone for targeting the nucleophilic cysteine residue [6b,12] . Several of these fragments displayed broad‐band inhibition of 3C and 3CL proteases [12a] and some were active in cellular virus proliferation assays, depending critically on the binding kinetics and chemical stability of the inhibitors [6b] . All these reported fragments, however, failed as inhibitors of SARS M pro .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Rademann and co‐workers also highlighted a superadditive fragment combination through a protein‐induced Mannich ligation [10] . Recent developments in protein‐templated chemistry also include the amidation from activated carboxylic acids and amines, [11] the Knoevenagel reaction, [12] and the Ugi four‐component reaction [13] …”
Section: Introductionmentioning
confidence: 99%
“…[7] More recently, Rademann and co-workers also highlighted a superadditive fragment combination through a protein-induced Mannich ligation. [10] Recent developments in protein-templated chemistry also include the amidation from activated carboxylic acids and amines, [11] the Knoevenagel reaction, [12] and the Ugi four-component reaction. [13] Other ligation strategies can be implemented by drawing inspiration from biocompatible and click chemistry portfolio reactions used in bioorthogonal bioconjugate processes, by tuning their kinetics to meet the requirements for use in KTGS strategies.…”
Section: Introductionmentioning
confidence: 99%